The Effect of the numbered head together and pair check cooperative learning models for the understanding of grammar - Rini Angreni Hasibuan; Syofyan Hadi; Rahmawati (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
The main purpose of the study was to determine the effect of using Numbered Head Together and Pair Check on structural understanding in eighth grade students of the Robi'ul Islam Islamic boarding school. This study used quantitative research using experimental methods. Data collection are tests and observations. Data analysis is used with normality, homogeneity and hypothesis test. The results of this study show that the understanding of structure before using Numbered Head Together and Pair Check is still low. With pre-test results in the experimental class obtained a an average score of 61.25 and in the control class an average score of 62.8. As for the use of cooperative learning Numbered Head Together and Pair Check in structure learning with a value of 3.4% very good. Then the post-test results in the experimental class got an average of 82.03 and in the control class got an average value of 73.3. and the result of hypothesis using the t-test obtained thitung = 4.047 and ttable = 2000 . If tcount > ttable or 20000> 4.046, accept Ha. The conclusion that Ha = Ha = means that there is Effect of the numbered head together and pair check cooperative learning models for the understanding of grammar VIII students at the Robi'ul Islam Islamic boarding school, Pasar Latong.